Механізм узгодженого управління регулюванням строків доставлення вантажів у транспортний вузол - Мурад'ян, Арсен Олегович (НТУ "ХПІ", 2017)
У статті досліджуються найбільш приваблива концепція розробки механізму оперативного регулювання строків доставлення вантажів, а також подавання рухомого складу у транспортні вузли. Механізм узгодження управління процесом перевалки вантажів в режимі оперативного регулювання цілком відповідає практично актуальним варіантам взаємодії суб'єктів транспортного вузла з логістичним оператором, що беруть участь в організації та здійсненні процесу обслуговування вантажів і рухомого складу в межах транспортних вузлів і на підходах до них.

In the article the most attractive concept of working out of the mechanism of operational regulation of terms of delivery of cargoes, and also feeding of rolling stock into transport nodes is investigated.The mechanism of management coordination of cargo handling process in the mode of operation-al regulation fully corresponds to virtually actual variants of interaction between the entities of the transport hub with the logistics operator involved in the organization and implementation of the process of servicing freight and rolling stock within the transport nodes and approaches to them. It was found that the proposed approach should be realized in two stages: first it is necessary to coordinate cargo transshipment process parameters, and then ensure optimal implementation of this process.The provisions set forth in the paper have theoretical significance since they are characterized by scientific novelty and are useful in practical terms as they improve operation efficiency both of transport hubs, and their customers.
Modelling and optimization of cargo transfer process in transport hubs
Keywords: перевалка вантажа; засіб транспортний; компанія стивідорна; управління залізниць; вантажовласник; оператор логістичний; cargo handling; vehicles; stevedoring company; railways management; cargo owner; logistics operator